Overexpression of a B-type cytokinin response regulator (OsORR2) reduces plant height in rice. (2nd August 2020) - Shi, Fachao; Wang, Min; An, Yuxing
ABSTRACT: Cytokinin plays crucial roles in regulating plant growth and development, with the signal transduction mediated by type-A and type-B response regulators (RRs).While much genetic knowledge about RRs on regulating plant height remains unclear. Here, we found that overexpressing an OsORR2 gene (a type-B RR) could reduce plant height in rice compared with the wild type (WT). Using quantitative real time (RT-qPCR) assay, OsORR2 was expressed widely in most tissues such as root, culm, sheath, leaf, and panicle. Strong signals were detected in leaf mesophyll cells and anther by in situ hybridization assays (ISH). The subcellular localization of OsORR2 was in cell nucleus. In addition, we found that the transcriptional expression levels of type-A RR genes such as OsRR9, OsRR10, OsRR12, and OsRR13 were significantly up-regulated in the overexpression transgenic plants (OE) plants. Taken together, our data suggested that OsORR2 was involved in the development of plant height in rice and provided a foundation for future deep molecular research of the type-B RRs.